Preferences for cervical cancer screening service attributes in rural China: a discrete choice experiment - Li, S; Liu, S; Ratcliffe, J; Gray, A; Chen, G (Dove Medical Press, 2019)
Objectives: Compared with other cancers, screening for cervical cancer is highly cost-effective. However, due to limited awareness about cervical cancer and many other factors, women’s attendance rate in rural China for cervical cancer screening remains low. This study aimed to determine women’s preferences for cervical cancer screening, to help enhance screening uptake. Methods: A discrete choice experiment (DCE) was conducted among a population-based random sample of 420 women (30–65 years old) in August 2015. Attributes included the percentage of cervical cancer-related death reduction, screening interval, screening location, screening pain, waiting time for screening results and out-of-pocket costs. Mixed logit models were used to analyze the relative importance of each screening attribute. Results: When considering a screening program, the screening cost, location and the percentage of cervical cancer-related death reduction were of most concern to women. Among the presented attributes, the pain associated with the process of screening was of the least concern. Conclusions: All six attributes in our study were found to have a large influence on the preference for cervical cancer screening, and significant preference heterogeneity existed among participants. The findings indicate that the maintenance of a free screening program is essential to increasing screening uptake in this vulnerable population.